2020
DOI: 10.1159/000512108
|View full text |Cite
|
Sign up to set email alerts
|

Celiac Disease and Sensitization to Wheat, Rye, and Barley: Should We Be Concerned?

Abstract: <b><i>Background:</i></b> Concomitance of celiac disease (CD) and IgE-mediated wheat allergy is described in some case reports. The objective was to evaluate the frequency of sensitization to wheat, rye, barley, and malt in children and adolescents with CD. <b><i>Methods:</i></b> Measurement of serum levels of specific IgE to wheat, rye, barley, and malt (ImmunoCAP; sensitization IgE ≥0.35 kUA/L) in CD patients followed in specialized clinics to verify allergy hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 29 publications
0
14
0
Order By: Relevance
“…An analysis of six original studies ( Table 2 ) revealed a possible coexistence of CD and A-IgE in four of them; however, two of them did not confirm this correlation. Among the papers confirming the possibility of an A-IgE occurrence in subjects with CD, two papers concerned allergies [ 14 , 15 ] and another two concerned sensitization [ 12 , 16 ]. Among the studies included in the analysis, there were four prospective [ 14 , 15 ] and two retrospective research studies [ 12 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An analysis of six original studies ( Table 2 ) revealed a possible coexistence of CD and A-IgE in four of them; however, two of them did not confirm this correlation. Among the papers confirming the possibility of an A-IgE occurrence in subjects with CD, two papers concerned allergies [ 14 , 15 ] and another two concerned sensitization [ 12 , 16 ]. Among the studies included in the analysis, there were four prospective [ 14 , 15 ] and two retrospective research studies [ 12 , 16 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the papers confirming the possibility of an A-IgE occurrence in subjects with CD, two papers concerned allergies [ 14 , 15 ] and another two concerned sensitization [ 12 , 16 ]. Among the studies included in the analysis, there were four prospective [ 14 , 15 ] and two retrospective research studies [ 12 , 16 ]. Five of the six studies were conducted in Europe [ 12 , 14 , 15 , 17 , 18 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations